ROUTINE SEQUENCING OF PATIENTS’ ENTIRE GENOME? SOME LEGAL THOUGHTS - NOIVILLE, Ch. (MEDECINE LEGALE DROIT MEDICAL, 2025)
As our developed societies enter the era of genomic medicine, as they promise a democratized access to whole genome sequencing for our benefit, they have to face a slew of ethical and legal questions. Drawing on the french « Plan France médecine génomique 2025 », the present article outlines some of these salient issues.